2012
DOI: 10.1159/000342256
|View full text |Cite
|
Sign up to set email alerts
|

Adherence Issues in Inherited Metabolic Disorders Treated by Low Natural Protein Diets

Abstract: Common inborn errors of metabolism treated by low natural protein diets [amino acid (AA) disorders, organic acidemias and urea cycle disorders] are responsible for a collection of diverse clinical symptoms, each condition presenting at different ages with variable severity. Precursor-free or essential l-AAs are important in all these conditions. Optimal long-term outcome depends on early diagnosis and good metabolic control, but because of the rarity and severity of conditions, randomized cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
91
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(97 citation statements)
references
References 76 publications
1
91
0
5
Order By: Relevance
“…Serum concentrations of folate were frequently in excess of the RR (65% above the UTI), as previously reported [12], particularly in older children. There is emerging evidence that excessive intakes of folate may be associated with an increased risk or enhanced progression of some cancers and pre-malignant lesions [11,12,13,14,15,16,17]. As micronutrient-supplemented L -amino acids provide the majority of nutrition in a low-phenylalanine diet, it is essential that the efficacy of any change to micronutrient profiles be assessed.…”
Section: Discussionsupporting
confidence: 81%
“…Serum concentrations of folate were frequently in excess of the RR (65% above the UTI), as previously reported [12], particularly in older children. There is emerging evidence that excessive intakes of folate may be associated with an increased risk or enhanced progression of some cancers and pre-malignant lesions [11,12,13,14,15,16,17]. As micronutrient-supplemented L -amino acids provide the majority of nutrition in a low-phenylalanine diet, it is essential that the efficacy of any change to micronutrient profiles be assessed.…”
Section: Discussionsupporting
confidence: 81%
“…In both years preceding start of GPB treatment, the patient required monthly hospitalizations. Although it cannot be excluded that the improvement was purely spontaneous, this is unlikely given the following considerations: patients with inherited metabolic disorders tend to become unstable during adolescence and numbers of decompensations often increase (MacDonald et al 2012). Further, the response to the change in drug treatment was rather prompt rendering a purely age-related effect unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that growth response on GH treatment is positively influenced by a young age at the start of treatment (Ranke et al 2007). Moreover, optimal long-term outcome, such as stature, in inherited disorders depends on early diagnosis and good metabolic control (MaCdonald et al 2012). Our patient was treated by 7 years of age, and chronic dysmetabolism and delayed rhGH therapy could be responsible for growth impairment.…”
Section: Discussionmentioning
confidence: 89%